Some aspects of Ottoman rule in Syria in the second half of the nineteenth century : reforms, Islam and Caliphate - Abū Mannah, B (1971)
The central theme of this thesis is the impact on Syria of the acts and policies of the Tanzimat period especially after 1860. But in order to understand the background of those policies it was necessary to shed fresh light on the social and political outlook of those bureaucrats who stood at the head of the state at the time of the Tanzimat period and on certain currents of thought which emerged curing that period. It appears that the basic question which busied Ottoman Muslims was the moral and legal basis of the state. Under the impact of the teachings of the Naqshbandi and possibly other orthodox orders, the causes of the decline of the state and of the degeneration of Muslim society were attributed to a disregard of shari‘a rules and to the rise of arbitrary government, In Istanbul and the Asiatic provinces a strong tendency emerged to restore the supremacy of the shari‘a in society and state and to end arbitrary rule. The reforms in their early period (1826-1854) seem to have been undertaken with this object in mind. About the same time it appears that the title of Caliph as applied to the sultan began to assume a new importance with emphasis upon the sultan being a just and shari‘a abiding ruler. Continued in thesis